Effects of Ni2+ substitution on the crystal structure, bond valence, and microwave dielectric properties of BaAl2–2xNi2xSi2O8–x ceramics. Issue 4 (April 2021) - Li, Chao; Ding, Shihua; Zhang, Yun; Zhu, Hui; Song, Tianxiu
Abstract: BaAl2−2 x Ni2 x Si2 O8− x ( x = 0, 0.005, 0.01, 0.02, 0.03) ceramics were prepared using traditional solid phase reaction method. The microwave dielectric properties, including permittivity ( ε r ), quality factor ( Q × f ), and temperature coefficient of resonant frequency ( τ f ), were discussed based on the bond valence theory. The first-principle calculation was adopted to determine the site (Ba, Al, and Si) where doping element (Ni 2+ ) would be inclined to occupy. The substitution of Ni 2+ for Al 3+ contributed to the breaking of Al-O and Si-O bonds and then facilitated the BaAl2 Si2 O8 (BAS) hexacelsian-celsian transformation. Moreover, this substitution could change the bond strength between cation and oxygen anion due to the variation of the bond valence, which reasonably explained the variation of ε r, Q × f, and τ f values. Well-sintered and completely transformed celsian ceramics can be obtained after doping with Ni 2+ . When x = 0.01, compact BaAl1.98 Ni0.02 Si2 O7.99 ceramic exhibited highly promising microwave dielectric properties: ε r = 6.89, Q × f = 53, 287 GHz and τ f = -25.31 × 10 −6 /°C.